The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/apha.13368
|View full text |Cite
|
Sign up to set email alerts
|

Extended hypoxia‐mediated H2S production provides for long‐term oxygen sensing

Abstract: Aim Numerous studies have shown that H2S serves as an acute oxygen sensor in a variety of cells. We hypothesize that H2S also serves in extended oxygen sensing. Methods Here, we compare the effects of extended exposure (24‐48 hours) to varying O2 tensions on H2S and polysulphide metabolism in human embryonic kidney (HEK 293), human adenocarcinomic alveolar basal epithelial (A549), human colon cancer (HTC116), bovine pulmonary artery smooth muscle, human umbilical‐derived mesenchymal stromal (stem) cells and po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 79 publications
2
16
1
Order By: Relevance
“…Reducing ambient oxygen from 21% to 5% increased intracellular H2S (AzMC fluorescence), consistent with previous studies showing that oxygen-dependent metabolism of H2S is a mechanism for short-and long-term cellular oxygen sensing [7,11]. H2S is constitutively produced from cysteine catabolism via the transsulfuration pathway and metabolized in the mitochondrion, initially by the mitochondrial enzyme sulfur:quinone oxidoreductase [12].…”
Section: Cellular Oxygen and Sulfur Availabilitysupporting
confidence: 90%
See 3 more Smart Citations
“…Reducing ambient oxygen from 21% to 5% increased intracellular H2S (AzMC fluorescence), consistent with previous studies showing that oxygen-dependent metabolism of H2S is a mechanism for short-and long-term cellular oxygen sensing [7,11]. H2S is constitutively produced from cysteine catabolism via the transsulfuration pathway and metabolized in the mitochondrion, initially by the mitochondrial enzyme sulfur:quinone oxidoreductase [12].…”
Section: Cellular Oxygen and Sulfur Availabilitysupporting
confidence: 90%
“…If each cell produces 3 × 10 −16 mol of H 2 S per cell [23], intracellular H 2 S could theoretically increase to 200 µM in one hour if H 2 S was not metabolized. Mitochondrial oxidation of H 2 S to sulfate normally keeps pace with H 2 S production but this can quickly change as evidenced by the rapid rise in H 2 S associated with hypoxia [11] and by the longer term responses observed in the present and other studies [7]. While it is tempting to propose that MnP-oxidation diverts H 2 S generated from cysteine catabolism away from mitochondrial oxidation, this does not appear to be the case.…”
Section: Mnp Utilization Of Intracellular Sulfurcontrasting
confidence: 56%
See 2 more Smart Citations
“…24 Lastly, Olson et al found that cellular H 2 S is increased during extended hypoxia, probably functioning as a continuously active O 2 -sensing mechanism in several cells. 25 Protection from detrimental environmental influences has, without doubt, contributed to modern man living longer and healthier lives than ever before in human history. However, exposure to the natural environment has, in an increasingly urbanized world, often become a planned project to be undertaken at leisure.…”
Section: Environment and Exposurementioning
confidence: 99%